PENGARUH PERAWATAN RUTIN BAYI BARU LAHIR TERHADAP KEBERHASILAN INISIASI MENYUSU DINI DI RUANG PONEK RSUD KABUPATEN JOMBANG - Rini Hayu Lestari (Universitas Nahdlatul Ulama Surabaya, 2016)
Early initiation of breastfeeding today has become a new hope for the world of obstetrics as a life-saving alternative step mother and baby. However, in practice there are factors that lead to the failure to conduct such an early suckling insiasi implementation of routine care of the newborn. This study aims to determine the effect of routine newborn care to the success of early initiation of breastfeeding in hospitals PONEK Jombang whose implementation. This study used the Analytic korelastional research with cross sectional method. The population in this study were newborn babies born in hospitals PONEK Lounge Jombang and using purposive sampling the treated sample obtained all newborns vaginal qualified IMD and do not do routine maintenance BBL according to the stages. The results showed that the influence of routine maintenance There newborn to suckle Early initiation success in PONEK Hospital Jombang on April 27 to June 6, 2015. Concluded there is the influence of routine newborn care to the success of Early Initiation of Breastfeeding. From these results, health workers must increase efforts to prevent maternal deaths, childbirth, postpartum and improvement of maternal and child health programs.